The Development of Guided Inquiry-Based Solubility Equilibrium E-Module - Wijayadi, Andri Wahyu; Fitriyah, Lina Arifah; Manasikana, Oktaffi Arinna (Tarbiyah : Jurnal Ilmiah Kependidikan, 2022)
Solubility equilibrium is a basic material of chemistry that involve an abstract concept. The visualization of abstract concept can be presented using the electronic media in the form of pictures, videos, and animations. The guided inquiry is one of the right strategies to teach about solubility equilibrium. The purpose of this research was to develop, determine the validity and the eligibility of the guided inquiry-based solubility equilibrium e-module. This research used Borg and Gall’s development model with 5 stages, which were the product analysis, the initial product development, the expert validation and revision, the field trial, the trial result analysis, and the product revision. The product validity has a very valid criteria in terms of the material, media, and language expert assessment with the average percentages were 96,11%, 83,18%, 90,61%. The students’ response to the product showed that the product was very proper to used in the learning based on the average percentage of 90,61%. That meant the developed guided inquiry-based solubility equilibrium e-module could be one of the teaching materials for basic chemistry course.